Two-Semester Physics Course for Bachelors at Technical University - S. В. Pereslegin; A. A. Korolev; S. A. Kurashova (Moscow Polytechnic University, 2019)
The article discusses two major problems in teaching physics for students majoring in IT at a technical university: 1) the forced change in the course structure and content due to the reduction in the time allotted for studying physics from three to two semesters, and 2) the uneven educational background of applicants, due to the fact that when entering a university, the results of the Unified State Examination in physics are not taken into account. The article analyzes the experience of the Physics Training Center at the ITMO University in St. Petersburg on conducting additional consultations on the school curriculum materials and on the development and using of electronic educational materials. The relevance of courses that are concentric in their structure, created by colleagues from the other universities, is noted. The authors propose to organize training for first-year students in various educational tracks, depending on their starting level. The article emphasizes the importance of maintaining completeness and ideological value of the course when revising the structure and content. The following conceptual scheme of the course is proposed: elementary physics as axiomatic science, statistical physics, quantum physics, quantum field theory (general concepts). The experience of the development and using of electronic educational materials (lecture presentations, electronic summaries of lectures and exercises) at ITMO University is analyzed. Despite the fact that, in general, e-learning elements make it possible to compensate the lack of class time caused by the program changes, students learn e-courses at different levels. It is noted that the reason, apparently, lies in the psychological unreadiness of a number of students to switch to "blended learning". It is emphasized that in the mixed course creation the development of materials for assessing student performance and their final certification is a fundamentally new and time-consuming task, the preference is given to the traditional full-time exam. The authors consider that it expedient to preserve the traditional structure of the physics course at technical university.